Komposisi Musik Marango Pendekatan Tradisi Musik Runguih Panutuik Dari Dendang Ratok Paninggahan - Dwi Syahputra; Firman Firman; Asep Saepul Haris (Jurnal Musik Etnik Nusantara, 2023)
Ratok Paninggahan is an art form found in Nagari Paninggahan, Junjung Sirih District, Solok Regency, West Sumatra. in the middle of the house as an expression of sadness and disappointment and regret over the death of a family member. However, after the entry and development of Islam in Minangkabau, this activity is no longer functioned because it is contrary to Islamic teachings. This results in the disappearance of the ratok paninggahan existence in the death ritual. However, the local community is very enthusiastic about maintaining Ratok Paninggahan as part of their culture, so that Ratok Paninggahan can be present again in their community in a different context. The existence of ratok paninggahan in its supporting community has always experienced various developments that have brought ratok paninggahan into various changes. The phenomenon of changes in ratok paninggahan offers various interesting aspects to study, but in this paper it will be limited to two main things, namely how ratok paninggahan is presented and how ratok paninggahan functions in its supporting community. The method used is descriptive analysis method.